Advocacy strategies for human rights: the campaign for the moratorium on the death penalty. (26th July 2016) - Marchetti, Raffaele
Abstract : This article examines the different strategies used by transnational actors in advocacy against the death penalty. In particular, it studies the strategies adopted by the transnational campaign for the moratorium on capital punishment in view of the United Nations General Assembly vote of 2007 and subsequent years (2008, 2010, 2012, and 2014). The article shows that a variety of different strategies are used in the organizational, institutional, and communicative domains. Within the broader debate on norm diffusion, this article sheds light on the under-investigated area of specific tactics, which include horizontal networking, multilayered political lobbying, reason-based framing, and emotion-based story-telling, deployed by transnational activists to induce key actors to change their policy preference.